Answer:
Option b
Explanation:
The equation
has center in (0,0).
But the transformation
shifts the center of the equation to the point (5, -6).
Therefore, when applying
we will have the following equation translated.
.
Simplifying we have:
Now we expand
and
![(y + 6) ^ 2](https://img.qammunity.org/2020/formulas/mathematics/high-school/mvhlixwg8rl14vk9ay78wkajh648csx7do.png)
![4(x ^ 2 -10x +25) + 5(y ^ 2 + 12y +36) = 20\\\\4x ^ 2 -40x + 100 + 5y ^ 2 + 60y + 180 = 20\\\\4x ^ 2 + 5y ^ 2 -40x + 60y +260 = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/df01wyjgkdxu58a0pfv0wfmfqayk4o6jnc.png)
The equation of a circle has the form
![h(x-a) ^ 2 + q(y-b) ^ 2 = r](https://img.qammunity.org/2020/formulas/mathematics/high-school/373vcx3lqbyla1gxkfs808rg6gv8k5yerv.png)
For h = 1 and q = 1.
If
and
then the graph becomes an ellipse.
In this problem h = 4 and q = 5 therefore the figure is an ellipse